FACTORS CORRELATED TO THE UTILIZATION OF INTEGRATED SERVICE POST BY THE MOTHERS OF CHILDREN UNDER FIVE YEARS IN THE WORKING AREA OF MAMAJANG PUBLIC HEALTH CENTER MAKASSAR - lusiana lusiana (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Introduction : Integrated Service Post (Posyandu) is a basic health activity conducted from, by, and for community assisted by health officials in a working area of public health center in which one of its functions is to observe the growth and development of children under five years. The aim of the research is to determine the factors correlated to the utilization of integrated service post by the mothers of children under five years. Method: The research was a qualitative design study using analytic descriptive method with cross sectional study approach. The design was the measurement or observation of independent and dependent variables conducted once at a time. The sample consisted of 91 people and the data were analyzed using chi-square statistic test. Result : The results of the research indicate that there is no correlation between mothers' age and the utilization of integrated service post by the mothers of children under five years (p=0.357), while family support (p=0.000), education (p=0.002), and distance (p=0.000) are correlated to the utilization of integrated service post by the mothers of children under five years. Conclusion: Family support, education, and distance have a correlation with the utilization of integrated service post by the mothers of children under five years. It is suggested to increase more the awareness of the importance of utilization of integrated service post and cooperation with all parties involving health cadres, and community leaders.